Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How does 2 negatives make a positive?
I understand in maths that two negatives make positive eg.
-2 * -10 = 10.
But when you times a positive with a negative it’s not the case eg. 2 * -10 = -20.
I have always been able to do these sums no problem but I’ve never really fully understand why this is
12 Answers
- nbsale (Freond)Lv 63 years agoFavorite Answer
Keep in mind that the negative sign indicates the number is the additive inverse of what it's applied to. There are only two real number operations: addition and multiplication. Subtraction is the addition of the additive inverse, and division is multiplication by the multiplicative inverse. That may seem like it's over-complicating things, but it's really just getting back to the basic definition of the operations.
Looking at it this way also allows us to prove that the product of two negatives is a positive. It's not good enough to just say it's the way it is, or it's a rule or law of math. We need to demonstrate why this "rule" is consistent with the other definitions governing the number system.
First let's think about a negative times a positive.
Suppose you have (-2)(3). Why is this -6?
Well, if you take (2)(3) + (-2)(3) = 6 + (-2)(3), by the distributive property that's equal to
(2 + (-2))(3) = 0(3) = 0
So (-2)(3) is additive inverse of 6, or -6
Similarly, (2)(-3) works out to be the same thing, -6.
Now suppose you have (-2)(-3)
Consider (-2)(-3) + (2)(-3), which is equal to (-2 + 2)(-3) = 0
So (-2)(-3) must be the additive inverse of (2)(-3), which is -6.
So (-2)(-3) = +6
I hope this was helpful.
- Anonymous3 years ago
K = {ab + a(-b)} + (-a)(-b) = ab + {a(-b)} + (-a)(-b)}
= ab + {a + (-a)}(-b) = ab + 0(-b) = ab + 0 = ab
K = {ab + a(-b)} + (-a)(-b) = a{b + (-b)} + (-a)(-b)
= a(0) + (-a)(-b) = 0 + (-a)(-b) = (-a)(-b)
(-a)(-b) = ab.
- How do you think about the answers? You can sign in to vote the answer.
- ComoLv 73 years ago
The facts are :-
(+ ve) x (+ ve) = + ve
(+ ve) x (- ve) = - ve
(-ve) x (-ve) = + ve
(-ve) x (+ve) = - ve
- SarojLv 43 years ago
The principle is -1 x -1 = +1, -1 x (+1) = -1. Generally, the '+' sign is not written on the left side of the number. When no sign is mentioned on the left side of the number it is understood to be '+' sign, a positive number only.
-2 * -10 = 20 not 10 as mentioned by you. however, 2 * -10 = -20 is correct.
The justification for why the product of two negative numbers is a positive number can be observed in the analysis of complex numbers.
(Ans.)
- Daniel HLv 53 years ago
Might be something you'll just have to accept.
-a * b = -ab
a * -b = -ab
-a * -b = ab
Also: -2 * -10 = 20 not 10
- 3 years ago
The two negatives cancel each other out and make the positive. It's just one of the laws of math.